2015
DOI: 10.2903/j.efsa.2015.4140
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on nitrofurans and their metabolites in food

Abstract: Nitrofurans are antimicrobial agents not authorised for use in food-producing animals in the European Union. Nitrofurans are rapidly metabolised, occurring in animal tissues as protein-bound metabolites. The European Commission requested EFSA to provide a scientific opinion on the risks to human health related to the presence of nitrofurans in food and whether a reference point for action (RPA) of 1.0 µg/kg for the marker metabolites is adequate to protect public health. Data on occurrence of nitrofuran marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 286 publications
(394 reference statements)
0
31
0
Order By: Relevance
“…furazolidone, furaltadone, nitrofurantoin, nitrofurazone and nifursol) are broadspectrum antibiotics that are not authorised for use in food-producing animals in the EU. EFSA assessed the risk related to the presence of nitrofurans and their metabolites in food in 2015 (EFSA CONTAM Panel, 2015). The current assessment is based on that opinion.…”
Section: Nitrofuransmentioning
confidence: 99%
“…furazolidone, furaltadone, nitrofurantoin, nitrofurazone and nifursol) are broadspectrum antibiotics that are not authorised for use in food-producing animals in the EU. EFSA assessed the risk related to the presence of nitrofurans and their metabolites in food in 2015 (EFSA CONTAM Panel, 2015). The current assessment is based on that opinion.…”
Section: Nitrofuransmentioning
confidence: 99%
“…Major advances in rapid and robust "green chemistry" sample preparation methods are required to enable portable multiplex detection platforms suitable for novice ends users outside the laboratory and to improve sample turnaround times at inspection points. (v) There have recently been calls for a modern toxicological risk assessment of nitrofurans in food to be carried out [2] and, in particular, a comprehensive carcinogenicity study of SEM [3]. (vi) There remains a need to identify an alternative to SEM as the marker residue for nitrofurazone abuse due to potential other sources of SEM in food.…”
Section: Future Needsmentioning
confidence: 99%
“…They were used previously in livestock production for prevention and treatment of gastrointestinal infections and as growth promoters. Current evidence of the health risks posed by nitrofuran residues in our food has been thoroughly assessed in a recent Scientific Opinion published by the European Food Safety Authority [3]. EU Member States are required to test for the presence of nitrofurans in foodstuffs as part of their National Residues Monitoring Schemes and 3 rd countries exporting relevant foods to the EU are required to implement analogous control systems.…”
Section: Introductionmentioning
confidence: 99%
“…6 European Food Safety Agency (EFSA), has recently provided a scientic opinion on the risks to human health related to the presence of nitrofurans in food by taking 1.0 mg kg À1 as possible concentration in which a single nitrofuran marker metabolite is present in foods of animal origin due to insufficient data from monitoring. 7 An indication of the continuous violations is provided by the European Rapid Alert System for Food and Feed (RASFF) 8 online database that contains more than 800 notications since 2002. 7 The interest in researching the accumulation of these drugs or their metabolites in different animal tissues as well as on the analytical methods for their identication and determination is still actual concern.…”
Section: Introductionmentioning
confidence: 99%
“…7 An indication of the continuous violations is provided by the European Rapid Alert System for Food and Feed (RASFF) 8 online database that contains more than 800 notications since 2002. 7 The interest in researching the accumulation of these drugs or their metabolites in different animal tissues as well as on the analytical methods for their identication and determination is still actual concern. 9,10 Comparative new studies focused on the interaction of some nitrofuran antibiotics with bovine serum albumin by means of uorescence and FT-IR spectroscopy, circular dichroism, atomic force microscopy and molecular docking investigation showed that the conformation of bovine serum albumin can be changed and unfolded in the presence of nitrofurans.…”
Section: Introductionmentioning
confidence: 99%